MATRIKS REFLEKSIF TERGENERALISASI - Hendra Maryulis; Sri Gemawati; Asli Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
In this article we discusses a generalized reflexive matrix A that has a relation PAQ A  and , PAQ A   , m n C A   where , n n C P   and m m C Q   are two generalized reflection matrices. The discussion was continued by discussing the properties of generalized reflexive matrix, namely orthogonal-L, orthogonal-R and the linear least squares problems whose coefficient matrix is of the form a generalized reflexive matrix.